Figuring the feminine : the rhetoric of female embodiment in medieval Hispanic literature - Ross, Jill, 1961- (University of Toronto Press, 2008)
Figuring the Feminine examines the female body as a means of articulating questions of literary authority and practice within the cultural spheres of the Iberian Peninsula (both Romance and Semitic) as well as in the larger Latinate literary culture. It demonstrates the centrality in medieval literary culture of the gendering of rhetorical and hermeneutical acts involved in the creation of texts and meaning, and the importance of the medieval Iberian textual tradition in this process, a complex multicultural tradition that is often overlooked in medieval literary scholarship. This study adopts an innovative methodology informed by current theories of the body and gender to approach Hispanic literature from a femininst perspective.Jill Ross offers new readings of medieval Hispanic texts (Latin, Castilian, and Hebrew) including Prudentius' Peristephanon, Gonzalo de Berceo's Milagros de Nuestra Señora, Shem Tov of Carrión's Battle Between the Pen and the Scissors, and several others. She highlights ways in which these texts contribute to the understanding of gender in medieval poetics and foreground questions of literary and cultural import. Figuring the Feminine argues that the bodies of women are crucial to the working out of such questions as the unsettling shift from orality to literacy, textual instability, cultural dissonance, and the resistance to cultural and religious hegemony.